Demographic and Clinical Characteristics of Sexually Abused Children and Adolescents Referred to Child and Adolescent Psychiatry for Psychiatric Assessment - Demirkaya, Sevcan Karakoç; Küçükköse, Mustafa (The Bulletin of Legal Medicine, 2017)
Objectives: Child abuse has been a continuous, hidden health and social problem in all over the world. Identifying risk factors are crucial to implement protective services. In Turkey, data of the legal cases are still lacking. This study aims to assess the sociodemographic and psychiatric features of the sexually abused children who have been referred for forensic evaluation together with their identity issues. Materials and Methods: The forensic files of the sexually abused cases (tı 11: 9 boys, 32 girls) who had been referred to the child psychiatry outpatient clinic were evaluated. Psychiatric diagnoses in the files were based on the Schedule for Affective Disorders and Schizophrenia for School-age children- Turkish Version. Data on age, gender, socioeconomic status and diagnoses of the victims and characteristics of the abusers were gathered and analysed by descriptive statistical methods. Results: Mean age of the victims was 11.54±3.31 years. Socioeconomic levels of their families were mostly lower class with rate of 51.2%. All perpetrators were male with a mean age of 23 years (min 14; max 67). When the consanguinity of the abusers and victims were taken into consideration, it was found that they were intrafamilial (fathers and brothers rate:12.2%), close relatives (19.5%), distant relatives (22.0%), other familiar (such as neighbours, friends: 14.6%) and unfamiliar (24.4%) people for the victims. 19.5% of the victims had mental retardation. The most common diagnoses of the victims were posttraumatic stress disorder (46.3%), other anxiety disorders (17.1%), and major depression (24.4%). Conclusion: Identified risk factors for sexual abuse, determined as the result of this study, are being a female child, late childhood period, mental retardation, and low economic status. The abusers were males who were familiar to the child victims. Preventive measures should be implemented for the entire population, particularly involving the high- risk groups to avoid child abuse.